Pelatihan Aplikasi Perkantoran untuk Meningkatkan Keterampilan Kader Posyandu Anyelir 8 Perumnas Antang Kota Makassar - Nuraida Latif; Muhajirin Muhajirin; Mashud Mashud; Ramlah P; Markani Markani; Neneng Awaliah; Butsiarah Butsiarah (Pendidikan Matematika, FKIP Universitas Mataram, 2021)
Posyandu is the center of community activities in the effort to provide health services and family planning. These trained Posyandu cadres are not only seen from the way they handle maternal and child health but also have to be supported by their ability to use computers in administrative management and data processing. The method used in this community service activity is a combination of tutorials, practice, and discussion or question and answer, as well as evaluation to determine the level of absorption of the training material. The office application materials provided are Microsoft word, Microsoft excel, and Microsoft powerpoint. Office application program training activities for cadres of Posyandu Anyelir 8 Block 8 Perumnas Antang were carried out well and improved the skills of Posyandu Anyelir 8 Block 8 Perumnas cadres in the use of information technology.